2009
DOI: 10.1080/15459620903425642
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Production Systems on Swine Confinement Buildings Bioaerosols

Abstract: Hog production has been substantially intensified in Eastern Canada. Hogs are now fattened in swine confinement buildings with controlled ventilation systems and high animal densities. Newly designed buildings are equipped with conventional manure handling and management systems, shallow or deep litter systems, or source separation systems to manage the large volumes of waste. However, the impacts of those alternative production systems on bioaerosol concentrations within the barns have never been evaluated. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 38 publications
8
44
0
Order By: Relevance
“…Differences in lymphocyte proliferation may be induced by differences in the level of immune stimulation of pigs, because of differences in their microbial environment. Sawdust bedding and concrete floor usually marginally differ in the microbial composition of bioaerosols (Letourneau et al, 2010), but the access to an outdoor area might have provided a more diversified microbial environment, although the design of the area (roof, concrete floor, wire fencing) limited the contacts of pigs with wild animals and soil microorganisms. The fact that only LW pigs had an increased proliferation in C environment relative to E environment is in agreement with our leukocyte count and salivary cortisol data, and suggests that LW pigs' adaptive traits are more influenced by the environment than those of B pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in lymphocyte proliferation may be induced by differences in the level of immune stimulation of pigs, because of differences in their microbial environment. Sawdust bedding and concrete floor usually marginally differ in the microbial composition of bioaerosols (Letourneau et al, 2010), but the access to an outdoor area might have provided a more diversified microbial environment, although the design of the area (roof, concrete floor, wire fencing) limited the contacts of pigs with wild animals and soil microorganisms. The fact that only LW pigs had an increased proliferation in C environment relative to E environment is in agreement with our leukocyte count and salivary cortisol data, and suggests that LW pigs' adaptive traits are more influenced by the environment than those of B pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Field studies have also verified that swine/chicken farms that are equipped with slatted floors or systems that separate solid and liquid manure or remove feces regularly have better air quality than farms using conventional systems without separation. 9,20 Therefore, feces, especially chicken feces, should be removed quickly to minimize bacterial aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…4,10 Swine confinement buildings that are equipped with systems that separate solid and liquid manure have better air quality than conventional systems without such separation. 9 Workers who manually feed nursery pigs suffer from high exposure to airborne bacteria, odors, and H 2 S. 3,[11][12][13] Similarly, the size distribution and concentrations of particulates in swine buildings are affected by the degree of animal activity, ventilation, bedding materials, and floor type. 12, 13 Oppliger and co-workers 2 demonstrated that occupational exposure to inhalable dusts, endotoxins, and bacteria is related to the growth stage of the animals because the biomass of feces and feather dandruff increase drastically during fattening periods.…”
Section: Introductionmentioning
confidence: 99%
“…Because organic dusts from swine confinements contain bacterial DNA (9,11,12) and TLR9 recognizes unmethylated cytosine-phosphateguanine (CpG) oligodeoxynucleotides motifs in bacterial DNA (18), we hypothesized that TLR9 would perform a functional role. was Although we observed no statistically significant reduction in neutrophil, macrophage, and lymphocyte influx in ODEtreated TLR9 KO mice compared with WT mice (P .…”
Section: Exploring the Involvement Of Alternative Myd88-dependent Recmentioning
confidence: 99%
“…Recent studies identified an abundance and diversity of Gram-positive bacteria in animal feeding confinement operations (6,(9)(10)(11). Furthermore, Archaeobacteria and fungi have also been detected in varying amounts, depending on the geographic region (2,12).…”
mentioning
confidence: 99%